Colleges and schools-Lyles College of Engineering-Miscellaneous 130
Edwards AFB, CA.--Air Force Captain Brewster H. Shaw, a test pilot and instructor with the Air Force Test Pilot School here, picks up his parachute harness prior to a flight. Captain has been selected for astronaut duty by the National Aeronautics and Space Administration. (U.S. AIR FORCE PHOTO BY Mr. Ken Graeb)